Shaft angle corrections for rotor tests in a closed section wind tunnel - Boffadossi, M.; Valentini, M.; Vigevano, L. (My University, 2014)
The present work applies a recently developed method1 to compute, by means of coupled CFD/CSD simulations, the shaft angle corrections for closed section wind tunnel tests on trimmed isolated rotor configurations. A complete simulation of the rotor flow field in free-flight is performed, and the power coefficient CP is extracted. Then a set of simulations of the same rotor at the same trim state is performed in the closed section of Politecnico di Milano large wind tunnel at different shaft angles. The power coefficient is extracted from each simulation in order to evaluate the shaft angle which matches the CP value obtained in free-flight. The computations are performed using a trimmed actuator disc model with non uniform source distribution, coupling the CFD code ROSITA with the CSD code MBDyn. The methodology is applied spanning the available tunnel velocity range. Two different rotor trim conditions are evaluated: zero flapping angle trim and shaft moment trim. The achieved corrections for the two trimming options are compared and discussed.